Emphysematous Gastritis Worsened after Upper Endoscopy - Tae Un Kim; Su Jin Kim; Hwaseong Ryu; Jin Hyeok Kim; Joo Yeon Jang; Jeong A Yeom; Jieun Roh; Hee Seok Jeong; Byung Soo Park; Dong Il Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Emphysematous gastritis is an infectious disease in which air is formed in the gastric wall by gas-forming organisms. It is infrequently reported but can be fatal without early diagnosis and treatment. The stomach is rarely infected because of the acidity of the gastric secretions and the rich blood supply. Treatment should be aimed at covering gram-negative organisms and anaerobes using broad-spectrum intravenous antibiotics, and occasional surgical management in order to enhance survival. Risk factors are those that lead to disrupted mucosal integrity, such as corrosive injury, and those that result in an immunosuppressed condition, including diabetes mellitus, chronic kidney disease, immunosuppressive drug use, and subsequent invasion by gas-forming organisms. We experienced a case of emphysematous gastritis that worsened after endoscopy. Aeration during upper endoscopy examination can cause barotrauma to the gastric wall with impairment of the mucosal barrier, resulting in the spread of gastric wall infection to the whole body. Therefore, we report this case and provide relevant literature review to suggest that early endoscopic evaluation can lead to exacerbation of emphysematous gastritis.